2009
DOI: 10.1073/pnas.0812564106
|View full text |Cite
|
Sign up to set email alerts
|

Continuous dissolution of structure during the unfolding of a small protein

Abstract: The unfolding kinetics of many small proteins appears to be first order, when measured by ensemble-averaging probes such as fluorescence and circular dichroism. For one such protein, monellin, it is shown here that hidden behind this deceptive simplicity is a complexity that becomes evident with the use of experimental probes that are able to discriminate between different conformations in an ensemble of structures. In this study, the unfolding of monellin has been probed by measurement of the changes in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 44 publications
(48 reference statements)
6
62
0
Order By: Relevance
“…At equilibrium, several of these on-pathway intermediates were shown to form in a gradual manner depending on GuHCl, urea or Na2SO4 concentration or pH and temperature. Continuous, diffusive swelling was observed also in a time-resolved study of the unfolding of folding intermediates of monellin [60]. In contrast, hopping observed in a force spectroscopy experiment of ribonuclease H folding shows that a single activation barrier separates unfolded molecules from a MG intermediate, and that the corresponding transition is first order [61].…”
Section: Accepted Manuscriptmentioning
confidence: 79%
“…At equilibrium, several of these on-pathway intermediates were shown to form in a gradual manner depending on GuHCl, urea or Na2SO4 concentration or pH and temperature. Continuous, diffusive swelling was observed also in a time-resolved study of the unfolding of folding intermediates of monellin [60]. In contrast, hopping observed in a force spectroscopy experiment of ribonuclease H folding shows that a single activation barrier separates unfolded molecules from a MG intermediate, and that the corresponding transition is first order [61].…”
Section: Accepted Manuscriptmentioning
confidence: 79%
“…7,10,42 The study of the unfolding of scMN has shown that unfolding commences through the formation of a dry molten globule 43 and proceeds gradually and not in an all-or-none manner. 44 Until recently, there were only a few quantitative studies of the unfolding of dcMN at equilibrium, 37,45 but the recent development of a good expression system for dcMN 46 made it possible to make a detailed study of its unfolding at equilibrium in relation to that of scMN. 39 This has set the stage for quantitative studies of its folding mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…However, Kayser et al found it to be a particularly useful tool for studying structure-function relationships in monoclonal antibodies, which were found to have an unusually high Trp content [199]. Another use of Trp as a natural fluorophore for FRET is to probe protein folding/unfolding, an important yet poorly understood biological process [200][201][202]. For example, Jha et al used FRET to study the unfolding of a small protein, monellin [202].…”
Section: Natural Fluorophoresmentioning
confidence: 99%
“…Another use of Trp as a natural fluorophore for FRET is to probe protein folding/unfolding, an important yet poorly understood biological process [200][201][202]. For example, Jha et al used FRET to study the unfolding of a small protein, monellin [202]. The transition of this small protein, from an unfolded to a folded state, is not completely understood but by using a naturally occurring Trp and additionally labeling the protein with the FRET acceptor thionitrobenzoate, researchers were able to determine that monellin unfolds gradually rather than all in one motion [202].…”
Section: Natural Fluorophoresmentioning
confidence: 99%
See 1 more Smart Citation